ANALISIS PERHITUNGAN HARGA POKOK PRODUKSI UNTUK MENENTUKAN HARGA JUAL PADA PABRIK ROTI DWI JAYA - Sufyanti Waruwu; Longginus Gelatan (Unit Pengelola dan Pengembangan Jurnal Ilmiah dan Informasi (UPPJII) STIE Jambatan Bulan, 2020)
This study aims to analyze and calculate the cost of production of various flavors of sweet bread and determine the selling price for each production unit based on the mark up desired by the Dwi Jaya Bread Factory by using the full costing method and variable costing. This research is a descriptive study with data collection techniques using interview and documentation techniques. The results showed that there were differences in the results of the calculation of the cost of goods manufactured and the selling price between the variable costing and full costing methods. The cost of production generated by the variable costing method is IDR 1,146,940,000 with a selling price of IDR 1,300. Meanwhile, the cost of production generated by the full costing method is IDR 1.261.115.916 with a selling price of IDR 1,445.